Monitoramento de aloanticorpos HLA em pacientes renais transplantados da região Norte/Noroeste do Estado do Paraná, Sul do Brasil - Almeida, Ayla Carolina de (2017)
The rejection process that can take the loss of the renal graft after transplantation starts with an immune response of the receptor against the transplanted organ, being the HLA system one of the main involved in this process. In this study, the presence of HLA alloantibodies in the pre and post renal transplantation was monitored in patients from the North and Northwest region of Paraná, Brazil. A total of 103 patients undergoing renal transplantation were studied. HLA typing was performed using the polymerase chain reaction-oligonucleotide specific sequence (SSO-PCR) method, associated with Luminex technology and detection of HLA alloantibodies using the LabScreen methodology (One Lambda, Inc., Canoga Park, CA, USA). Among the 103 patients studied, 58 (56.4%) received a deceased donor graft, the remaining from a related live donor. In the pre-transplantation phase 40 (38.8%) of the patients presented HLA alloantibodies. Of these 40, 18 (45.0%) reacted to the Antibody Reactor Panel (PRA) for HLA-class I, 9 (22.5%) for class II and 13 (32.5%) for both classes. About PRA in the 6th month after transplantation, we observed that 71 (68.9%) patients had no antibodies and 32 (31.1%) patients had (PRA ≠ 0), and 17 (53.1%) had PRA Positive for class I, 5 (15.6%) for class II and 10 (31.3%) for both classes. In the 12th month after transplantation, of the 59 patients followed up, we observed that 42 (40.7%) patients presented no antibodies (PRA = 0) and 17 (59.3%) patients presented, of which 8 (47.0%) were positive for class I, 5 (29.4%) for class II and 4 (23.6%) for both. In patients monitored for 6 months, an increase in the percentage of PRA for class I was observed in 11.6%, decrease in 19.4% and unchanged in 68.9% when compared to PRA before transplantation. For class II, there was an increase in PRA in 3.9% of patients, a decrease of 15.5% and an unchanged rate of 80.6%. In patients monitored for 12 months, an increase in the percentage of PRA for class I was observed in 11.9%, decrease in 11.9% and unchanged in 76.3%. For HLA class II there was an increase in the percentage of PRA in 6.8%, decrease in 13.6% and unchanged in 79.7%. In two groups of patients monitored, there was a higher percentage of PRA reduction in patients over 50 years of age when compared to those up to 50 years of age. This study may contribute to the understanding of the kinetics of HLA alloantibody production and to minimize the rejection processes through an individualized immunosuppression.